Socio-geographical aspects of formation of the general educational complex of regions of Ukraine - Bilous, Yuriy (Journal of Education, Health and Sport, 2021)
The article considers spatial differences in the development of the general educational complex. The main indicators that characterize the level of development of the general educational complex are the coefficient of concentration, the coefficient of localization, social density, the quality of students’ knowledge, the number of teachers, and others. Based on these indicators, 5 groups of regions were identified according to the level of development of the general educational complex using Kohonen’s self-organizing feature map. As of January 1, 2020, there were 14,815 general secondary education institutions inUkraine, with 437,981 teachers and more than 4 million students. In general, inUkraine, there is significant spatial differentiation in the level of development of general secondary education, which contradicts the principles of equality and access to quality educational services.